Theoretical Dimension of Modern Designers’ Conceptual Forms of Creativity - Oksana Lahoda (Культура і мистецтво у сучасному світі)
The aim of the article is to identify key characteristics of artistic and design practices interaction; to define directions of conceptual design development based on the results of analysing scientific and theoretical foundations of conceptualism as a special form of the artists’ creativity in the 20th century. Results. It is demonstrated that the focus of modern designers on conceptual forms of creativity is explained by the fact that they contribute to forming unique authors’ projects of aesthetic and value content, innovative searches in the context of cultural and civilisational shifts. A conceptual costume of the beginning of the 21st century is a kind of mediator between art practices of conceptual art and design practices in the sphere of project culture, synthesising social and psychological aspects of fashion, social and symbolic functions of clothing. A conceptual design narrativises philosophical, artistic and technological aspects of design, enriching design products with an expressive metaphoricity. It is revealed that in modern art history a clear definition of the term system of the conceptual direction in design has not been formed till now. The research of this complex phenomenon, synthesised by fashion and artistic clothing design, requires a complex interdisciplinary approach. The conceptual costume is studied as an art-design object from the standpoint of global and local tendencies in the society development, which declare certain worldview values in the form of a visual metaphor. Scientific novelty. For the first time, the theoretical understanding of the conceptual costume grounds on the interaction of design with culture and art as a special space of its direct functioning, which makes it possible to form project conceptualism as a special methodology. Conclusions. The authors’ concepts in the costume are extrapolated in different ways: as visual quotations or metaphors; as a transformation of the art object idea into the form of the costume. Actually, they need in-depth and detailed studying.